1996
DOI: 10.1088/0953-4075/29/21/026
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of atomic cluster - cluster collisions

Abstract: A theoretical study on collisions between fullerenes for the systems C + 60 + C 60 , C + 70 + C 60 and C + 70 + C 70 is presented covering a wide range of collision energies (50 < E < 250 eV in the centre-of-mass frame). Quantum molecular dynamics (QMD) simulations enable a detailed insight into the underlying mechanism of the different reaction channels. The fusion barriers for the investigated systems are determined and compared with experimental data taking into account the finite temperature of the collidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…This can be regarded as an average probability for fusion to occur in the reactions after all the energetic and impact parameter constraints have been taken into account by the model. Detailed quantum molecular dynamic (QMD) simulations [13] have shown that this is due to a "bouncing off " mechanism which is a consequence of the strongly directional covalent bonding in the fullerene cage. Trajectories at the same collision energy and impact parameter can lead to very different results depending on the relative orientation of the hexagons and pentagons in the two colliding fullerenes.…”
Section: -Fusion and Fragmentation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be regarded as an average probability for fusion to occur in the reactions after all the energetic and impact parameter constraints have been taken into account by the model. Detailed quantum molecular dynamic (QMD) simulations [13] have shown that this is due to a "bouncing off " mechanism which is a consequence of the strongly directional covalent bonding in the fullerene cage. Trajectories at the same collision energy and impact parameter can lead to very different results depending on the relative orientation of the hexagons and pentagons in the two colliding fullerenes.…”
Section: -Fusion and Fragmentation Reactionsmentioning
confidence: 99%
“…A better fit to the experimental data in the barrier region is found by using an extension to the absorbing sphere model which takes into account the steric effects [8][9][10][11][12][13]. This model can reproduce the curvature of the experimental data points near the threshold if the fusion probability is assumed to be approximately proportional to the collision energy [8].…”
Section: -Fusion and Fragmentation Reactionsmentioning
confidence: 99%
“…Our systematic investigation of fullerene-fullerene collisions using QMD simulations includes at present C + 60 + C 60 [5,6], C + 70 + C 60 and C + 70 + C 70 collisions [4]. In this section, the fusion-relevant range of collision energies 50 E cm 250 eV (in the centerof-mass frame) is considered.…”
Section: -Collisions Between Fullerenesmentioning
confidence: 99%
“…1) due to the rearrangement of atoms in the contact zone, a fusion event will be detected, whereas if the increase of kinetic energy proceeds to a large enough extent (lower left part of fig. 1) the effective repulsion of the (more or less) intact fullerene structure leads to a scattering event [4]. In fusion events, strongly deformed (and highly excited) compound clusters are formed which resemble a "peanut"-like structure (see upper right part of fig.…”
Section: -Collisions Between Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation